Pengaruh Sosialisasi Perpajakan,Penagihan Pajak dengan Surat Teguran Pajak,dan Pemeriksaan Pajak terhadap Kepatuhan Wajib Pajak yang Dimoderasi oleh Pemahaman Pajak - Sarmauli Silalahi; Vinola Herawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Taxes are the largest source of state income and have an important role in the country's economy. The aim of this research is to empirically prove the influence of tax socialization, tax collection with tax warning letters, and tax audits on taxpayer compliance which is moderated by tax understanding. This research uses a non-probability sampling technique with purposive sampling. The sample in this research consisted of 100 taxpayers. Hypothesis testing uses SmartPLS 3.0 tools or software. Based on the results of the tests carried out, the research results show that Tax Socialization has an effect on Taxpayer compliance, Tax Collection with a Letter of Warning has an effect on Taxpayer compliance, Tax Inspection has an effect on Taxpayer compliance, There is no influence between Tax Socialization moderated by Tax Understanding on Taxpayer Compliance , There is no influence between Tax Collection and Warning Letters moderated by Tax Understanding on Taxpayer Compliance, and there is no influence between Tax Audits moderated by Tax Understanding on Taxpayer Compliance.